2007
DOI: 10.1016/j.fertnstert.2007.01.008
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of dehydroepiandrosterone sulfate on steroid receptors, aromatase, cyclooxygenase-2 expression, and steroid hormone production in preovulatory human granulosa cells

Abstract: DHEAS may be an essential trigger of ovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…According to this finding, it has been reported that an excess of androgens leads to more prolonged sexual cycles in PCOS patients by rescuing the CL from luteolysis (Manikkam et al 2006). The ability of DHEA to stimulate E 2 secretion has also been previously reported in human granulose cells (Bonser et al 2000), and the mechanism proposed is the enhanced expression of P450 aromatase by DHEA (Elbeltagy et al 2007). Moreover, Genazzani et al (2006) have recently reported that administration of DHEA in postmenopausal women is capable of increasing circulating levels of androgens and progestins.…”
Section: Discussionmentioning
confidence: 74%
“…According to this finding, it has been reported that an excess of androgens leads to more prolonged sexual cycles in PCOS patients by rescuing the CL from luteolysis (Manikkam et al 2006). The ability of DHEA to stimulate E 2 secretion has also been previously reported in human granulose cells (Bonser et al 2000), and the mechanism proposed is the enhanced expression of P450 aromatase by DHEA (Elbeltagy et al 2007). Moreover, Genazzani et al (2006) have recently reported that administration of DHEA in postmenopausal women is capable of increasing circulating levels of androgens and progestins.…”
Section: Discussionmentioning
confidence: 74%
“…Theses levels were particularly high with respect to the concentrations usually found (Van Eenoo et al, 2001; Hemmersbach et al, 2006). For this woman, further analysis detected a high serum level of DHEAs, which may have induced an increase in ovarian aromatase activity (ElBeltagy et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…However, this possible association requires further evaluation. Elbetagy et al [23] treatment of granulosa cells with low dose DHEAS increased the expression of androgen receptor, aromatase, 3-beta-hydroxysteroid dehydrogenase, and cyclooxygenase-2, reduced the expression of estrogen receptor beta, and increased estrone and estradiol levels. To sum up, DHEA not only has a beneficial effect on the percentages of primordial follicles but also affects the steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%